Computational Continuum Mechanics of Nanoscopic Structures Nonlocal Elasticity Approaches - Ghavanloo, Esmaeal; Rafii-Tabar, Hashem; Fazelzadeh, Seyed Ahmad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers a comprehensive treatment of nonlocal elasticity theory as applied to the prediction of the mechanical characteristics of various types of biological and non-biological nanoscopic structures with different morphologies and functional behaviour. It combines fundamental notions and advanced concepts, covering both the theory of nonlocal elasticity and the mechanics of nanoscopic structures and systems. By reporting on recent findings and discussing future challenges, the book seeks to foster the application of nonlocal elasticity based approaches to the emerging fields of nanoscience and nanotechnology. It is a self-contained guide, and covers all relevant background information, the requisite mathematical and computational techniques, theoretical assumptions, physical methods and possible limitations of the nonlocal approach, including some practical applications. Mainly written for researchers in the fields of physics, biophysics, mechanics, and nanoscience, as well as computational engineers, the book can also be used as a reference guide for senior undergraduate and graduate students, as well as practicing engineers working in a range of areas, such as computational condensed matter physics, computational materials science, computational nanoscience and nanotechnology, and nanomechanics.
From the content: Fundamental tenets of nanomechanics -- Fundamental notions from classical continuum mechanics -- Essential concepts from nonlocal elasticity theory -- Nonlocal modelling of nanoscopic structures -- Elastic properties of carbon-based nanoscopic structures.
Keywords: Mechanics, Applied; Solids; Nanotechnology; Mathematical physics; Biotechnology; Solid Mechanics; Nanotechnology; Theoretical, Mathematical and Computational Physics; Biotechnology